2004 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) (IEEE Cat. No.04CH37566)
DOI: 10.1109/iros.2004.1389563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of auditory and visual modalities on skin potential response to robot motions

Abstract: Alshacl-This paper addresses the issue or investigating the relationship between Skin Potential Response (SPR) and robol motion from the aspect of auditory and visual modalities. The motion of the robotic devices primarily gave stimulus lo the human thmugh the auditory and visual modalities. Our previous work indicated that actuation noise caused from the robots tended to raise the sympathetic nerve system response ofthe heart rate variability. However it was diilicult to evaluate instantaneous response corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Industrial manipulators constitute the type of robot on which the largest number of papers were written on perceived safety in pHRI. Earlier works used standard industrial manipulators, and precisely CRS A460 [20,21,[23][24][25], Mitsubishi Movemaster RM-501 [18,19,22], ABB IRB-120 [29,31], Comau SMART SiX [27], Yaskawa MOTOMAN-K10S and SONY SRX-410 [28]. More recent papers, instead, started using collaborative robots: KUKA LBR iiwa [35,38,43], Kinova MICO [33], UR3 [44], UR5 [39], UR10, [30], Sawyer [45], and Franka Emika Panda [42].…”
Section: Overview On Industrial Manipulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Industrial manipulators constitute the type of robot on which the largest number of papers were written on perceived safety in pHRI. Earlier works used standard industrial manipulators, and precisely CRS A460 [20,21,[23][24][25], Mitsubishi Movemaster RM-501 [18,19,22], ABB IRB-120 [29,31], Comau SMART SiX [27], Yaskawa MOTOMAN-K10S and SONY SRX-410 [28]. More recent papers, instead, started using collaborative robots: KUKA LBR iiwa [35,38,43], Kinova MICO [33], UR3 [44], UR5 [39], UR10, [30], Sawyer [45], and Franka Emika Panda [42].…”
Section: Overview On Industrial Manipulatorsmentioning
confidence: 99%
“…In addition to the previous categorization, papers [17, 20, 21, 23-26, 28, 29, 31-33, 35, 36, 38-40] focused on finding a connection between perceived safety, robot speed, and relative distance between human and robot, with [27,30,40] having an explicit focus on motion prediction. The human attitude toward robot position and approach direction was studied in [18,25]. Finally, the effect of visibility/audibility of the robot by the human subjects were analyzed in [18,22].…”
Section: Overview On Industrial Manipulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work indicated that actuation noise come from the robots tended to raise the sympathetic nerve system (SNS) response of the heart rate variability (HRV) [4]. In another experiment we used electrodermal activity (EDA) to evaluate the SNS response [1] for the reason that HRV analysis which processed data in frequency domain claimed data acquisition for more than 25 seconds. Alternatively, the signals related to EDA respond to the stimulus instantaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work indicated that actuation noise from the robots tended to raise sympathetic nervous system (SNS) response of heart rate variability (HRV) [12]. In another experiment we used electrodermal activity (EDA) to evaluate SNS response [13] because the HRV analysis of data in the frequency domain claimed data acquisition for more than 25 seconds. Alternatively, the signals related to EDA respond to the stimulus instantaneously.…”
Section: Introductionmentioning
confidence: 99%